Disrupting terrorist assassinations through situational crime prevention - Mandala, Marissa (Crime & delinquency, 2018)
This article uses environmental criminology and situational crime prevention (SCP) to devise a series of hypotheses to determine the factors that distinguish successful from unsuccessful assassination incidents. We analyzed a random sample of 100 successful and 100 unsuccessful assassination incidents from the Global Terrorism Database (GTD) that occurred between 2005 and 2014. We then consulted open sources to create new SCP variables that we added to the original GTD data. The hypotheses were tested in a binary logistic regression. Results show that successful assassinations are associated with several SCP measures, including weapon type, fatalities, terrorist proximity to target, and attack and target location.